2018
DOI: 10.1200/edbk_200573
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Oligometastatic Soft Tissue Sarcoma

Abstract: Soft tissue sarcomas (STS) encompass a group of rare but heterogeneous diseases. Nevertheless, many patients, particularly those with oligometastatic disease can benefit from thoughtful multimodality evaluation and treatment regardless of the STS subtype. Here, we review surgical, interventional radiology, radiation, and chemotherapy approaches to maximize disease palliation and improve survival, including occasionally long-term disease-free survival. Surgical resection can include lung or other visceral, soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 83 publications
0
11
0
1
Order By: Relevance
“…Although these tumours are sometimes mistakenly called "radio-resistant", radiotherapy can alleviate metastatic patients' symptoms such as metastasis pain and haemoptysis. Image-guided radiotherapy is more advantageous than surgery in patients with oligometastatic disease, especially in sarcoma [3]. Therefore, radiotherapy is a critical part of the treatment of sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Although these tumours are sometimes mistakenly called "radio-resistant", radiotherapy can alleviate metastatic patients' symptoms such as metastasis pain and haemoptysis. Image-guided radiotherapy is more advantageous than surgery in patients with oligometastatic disease, especially in sarcoma [3]. Therefore, radiotherapy is a critical part of the treatment of sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…These interventional radiology procedures include radiofrequency, microwave and cryoablation, as well as arterial embolisation and IRE 4,5,31,32 . These techniques greatly vary in complexity and fundamental principles, and should only be applied within a shared multidisciplinary algorithm 33 . Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identified the benefits of ablation as a therapeutic option in the management of patients with sarcoma [12][13][14][15][16]. Ablation is minimally invasive, lacks treatment-specific toxicity, and provides a lower-morbidity treatment option compared to surgical resection [17,18]. For patients with metastatic sarcoma, while image-guided ablation may extend the chemotherapy-free interval, it remains unknown how long ablation could extend the chemotherapy-free interval.…”
Section: Introductionmentioning
confidence: 99%